Socioeconomic correlates of face mask use among pedestrians during the COVID-19 pandemic: An ecological study - Rahimi, Zahra; Mohammadi, Mohammad Javad; Araban, Marzieh; Shirali, Gholam Abbas; Cheraghian, Bahman (Frontiers in Public Health, 2022)
Background Many countries have recommended using face masks for the general population in public places to reduce the risk of COVID-19 transmission. This study aimed to assess the effects of socioeconomic status on face mask use among pedestrians during the COVID-19 pandemic. Methods This cross-sectional study was conducted in Ahvaz, southwest Iran in August 2020. A total of 10,440 pedestrians have been studied from 92 neighborhoods of the city. Three socioeconomic indicators including Land price, Literacy rate, and the Employment rate for each neighborhood were used in this study. Analysis of Covariance and partial correlation coefficients were applied to assess the relationship between prevalence rates of mask usage and SES indicators. Results The mean ± SD age of the pedestrians was 32.2 ± 15.1 years. Of 10,440 observed participants, 67.9% were male. The overall prevalence of face mask usage was 45.6%. The prevalence of mask usage in older people and women was significantly higher than the others. The three assessed socioeconomic indicators were directly correlated to the prevalence of mask usage at individual and neighborhood levels. Conclusion We found that literacy had the strongest correlation with the prevalence of mask usage compared to the land price and employment rate among the three assessed SES indicators. Hence, it can be concluded that the social component of socioeconomic status has a greater effect on mask usage by people than the economic component of socioeconomic status.